Clinical characteristics of endometrial cancers with microsatellite instability-high and BRCA1/2 mutations - Shan, Yuping; Wang, Yan; Huang, Liying; Li, Guangqi; Cui, Zhumei; Xing, Xiaoming; Yin, Guangjie (Frontiers in Oncology, 2025)
ObjectiveThe purpose of this study was to identify the clinical features of endometrial cancers (EC) with microsatellite instability-high (MSI-H) and BRCA1/2 mutations (BRCAm).MethodsWe selected patients diagnosed with EC who were MSI-H from the Affiliated Hospital of Qingdao University between March 2021 and December 2024. The clinical information was collected after applying the inclusion and exclusion criteria. Based on BRCA1/2 status, we divided the patients into two groups: the MSI-H only group (M group), and the MSI-H and BRCAm group (MB group). After comparing the clinical characteristics of the two groups, Kaplan-Meier (K-M) curves were employed to analyze the distribution of progression-free survival (PFS) between them. Finally, both univariate and multivariate Cox proportional hazards regression models were utilized to assess various prognostic variables.ResultsA total of 177 patients were included in the final analysis, of whom 28 were identified as having BRCAm. The rate of laparoscopic surgery in M group was higher than that in MB group (87.25% vs. 67.86%, p-value=0.022). The lymph node metastasis rate in MB group was significantly higher than that in M group (14.29% vs. 2.01%, p-value=0.011). Additionally, a higher proportion of patients received immunotherapy in MB group (7.14% vs. 2.68%, p-value=0.011). The recurrence rates in M group and MB group were 1.34% and 17.86%, respectively (p-value=0.003). K-M analysis indicated that there was statistically significant difference in PFS between the two groups (p-value=0.006). Furthermore, we did not identify any independent risk factors that influenced prognosis in our study.ConclusionThe co-occurrence of BRCAm and MSI-H is associated with high rates of lymph node metastasis and recurrence. However, BRCAm was not an independent prognostic factor influencing PFS of EC with MSI-H.